Nephrogenic systemic fibrosis: Current concepts - Prasanta Basak; Stephen Jesmajian (Wolters Kluwer Medknow Publications, 2011)
Nephrogenic systemic fibrosis (NSF) was first described in 2000 as a scleromyxedema-like illness in patients on chronic hemodialysis. The relationship between NSF and gadolinium contrast during magnetic resonance imaging was postulated in 2006, and subsequently, virtually all published cases of NSF have had documented prior exposure to gadolinium-containing contrast agents. NSF has been reported in patients from a variety of ethnic backgrounds from America, Europe, Asia and Australia. Skin lesions may evolve into poorly demarcated thickened plaques that range from erythematous to hyperpigmented. With time, the skin becomes markedly indurated and tethered to the underlying fascia. Extracutaneous manifestations also occur. The diagnosis of NSF is based on the presence of characteristic clinical features in the setting of chronic kidney disease, and substantiated by skin histology. Differential diagnosis is with scleroderma, scleredema, scleromyxedema, graft-versus-host disease, etc. NSF has a relentlessly progressive course. While there is no consistently successful treatment for NSF, improving renal function seems to slow or arrest the progression of this condition. Because essentially all cases of NSF have developed following exposure to a gadolinium-containing contrast agent, prevention of this devastating condition involves the careful avoidance of administering these agents to individuals at risk.